A new species of Eugenia (Myrtaceae) from South America - Mazine, Fiorella; Faria, Jair Eustáquio Quintino De (Phytotaxa, 2013)
Eugenia densiracemosa, a new species from central Brazil to French Guiana, is described, illustrated and compared to the related Eugenia egensis, from which it is set apart by the longer inflorescences, longer rachis (1.2–6.0 cm long), with 9–25 pairs of flowers, while in E. egensis the inflorescences are smaller, with rachis 0.1–0.6 cm long, and a smaller number of flowers (1–4 pairs of flowers in each inflorescence).